Simulation of Southern Louisiana watershed hydrology with USDAHL-74 revised model of watershed hydrology - Saleh, Abdul Razak (Universiti Putra Malaysia Press, 1987)
The USDAHL-74 Revised Model of Watershed Hydrology was calibrated on a 0.86ha agricultural watershed in southern Louisiana.The input parameters determined in the calibrating period were used to simulate runoff from a nearby 1.55ha watershed. Differences between observed and simulated monthly runoff from the test watershed were not significant.